Orang Kristen Dan Problematika "Merokok" - Seru, Rika; Belo, Yosia; Putra, Adi (JURNAL LUXNOS, 2024)
Abstract: Smoking is a lifestyle that is often found in the practical lives of people, including Christians and even servants of God. This practice raises pros and cons, because the concept of the Bible does not explicitly teach about “no smoking”. Meanwhile, the church is divided on how to deal with it, some consider it no problem, but others see it as something that should not be done. This study was conducted to find a theological principle from the Bible to affirm that Christians do not smoke. Using a qualitative research or literature review approach, several theological reasons were found as follows: (1) the body was created in the image and likeness of God, (2) the body has also received redemption in Christ, and (3) the body will also be resurrected and glorified in eternity.